The place of hydroxychloroquine in modern dermatology - Aleksandra Dańczak-Pazdrowska; Adriana Polańska (Termedia Publishing House, 2021)
Hydroxychloroquine has been known since the 1940s. It was initially used to treat malaria. Currently, it has a well-established position in the treatment of lupus erythematosus. The knowledge about its benefits is increasing over time. The mechanism of action of hydroxychloroquine reaches far beyond the immunomodulatory effect, and includes a beneficial effect on glycemic control in patients with diabetes and it is believed to have an effect on normalization of lipid levels, including total cholesterol, LDL cholesterol and triglycerides. In treatment of lupus erythematosus hydroxychloroquine allows decreasing the dose of immunosuppressive drugs, thus not only increasing the treatment efficacy, but also reducing the risk of adverse effects. Possible indications for hydroxychloroquine include also granulomatous skin diseases, such as disseminated annular granuloma, cutaneous sarcoidosis, or reactive granulomatous dermatitis. This article discusses the current indications for hydroxychloroquine with focus on recommended therapeutic regimens and monitoring treatment.